If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 18 = 14 Reorder the terms: 18 + -3x = 14 Solving 18 + -3x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -3x = 14 + -18 Combine like terms: 18 + -18 = 0 0 + -3x = 14 + -18 -3x = 14 + -18 Combine like terms: 14 + -18 = -4 -3x = -4 Divide each side by '-3'. x = 1.333333333 Simplifying x = 1.333333333
| 7x+6y-2=22 | | 7x-4y=6 | | 6/9-1/12 | | 2x+5=39654 | | 2p+4p+6=36 | | m/-2-6=-9 | | 12p+5pd-3p+6pd=equation | | -8=3u+4 | | 6x+2(3x-9)=18 | | x+4.5=-8.7 | | 3x+5+4x+7=33 | | d+2h=24 | | 5m+6mn-(-9n)+2(m-n)=equation | | 1/3(9y-6)+2y=38 | | (8x+10)=0.5(12x+40) | | x+2/2=21/24 | | -8=.75x | | 3d+3h=45 | | x/2=x/5 | | 2y+10x=4 | | -4/5=-5t | | 2-x=7x+2 | | 4(2n-3)-6n=12 | | 9+a=30 | | 0.5x=0.25x+2 | | .66x-3=-13 | | 19+d=29 | | 0.15(x+2)=0.3+0.2x | | x+11/6=8 | | m+49=82 | | 2.40-1.20x=15 | | 2x^2+3x=28 |